Ketidakadilan Gender yang Dialami Pekerja Perempuan di Daerah Pariwisata: Gender Inequality Experienced by Female Workers in Tourism Areas - Siti Masrohatin (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2012)
Gender isn't a difference of sex or god's will, but is something that is oriented him and her by means of social and culture process in long term. The power of woman in tourism sector is very interesting to be soled. According to conventional, tourism sector is public sector, that is a man area, but a woman area is domestic sector. Based on tourism development in Bali, there are many jobs opportunity that can be entered by woman community. In fact it will be affected by gender problem. Gender problem in this paper is studied based on research in two villages which different development tourism at Ubud, Gianyar, Bali. The result of the research shows that the woman worker in tourism sector are discriminated which is reflected by lower level wage than man worker althoughthey have same education and or same job position. Gender bukanlah perbedaan jenis kelamin atau kehendak Tuhan, melainkan sesuatu yang dibentuk melalui proses sosial dan budaya dalam jangka panjang. Peran perempuan di sektor pariwisata sangat menarik untuk dibahas. Menurut konvensi, sektor pariwisata adalah sektor publik, yang merupakan wilayah laki-laki, sedangkan wilayah perempuan adalah sektor domestik. Berdasarkan pengembangan pariwisata di Bali, terdapat banyak peluang kerja yang dapat dimasuki oleh komunitas perempuan. Faktanya, hal ini akan dipengaruhi oleh masalah gender. Masalah gender dalam penelitian ini diteliti berdasarkan penelitian di dua desa yang memiliki pengembangan pariwisata yang berbeda di Ubud, Gianyar, Bali. Hasil penelitian menunjukkan bahwa pekerja perempuan di sektor pariwisata mengalami diskriminasi, yang tercermin dari upah yang lebih rendah dibandingkan pekerja laki-laki meskipun mereka memiliki pendidikan yang sama atau posisi pekerjaan yang sama.